Assessment of Age-Related Morphometric Changes of Subcortical Structures in Healthy People Using Ultra-High Field 7 Tesla Magnetic Resonance Imaging - Wang, Xue-Yuan; Zhao, Lei; Yu, Tao; Qiao, Liang; Ni, Duan-Yu; Zhang, Guo-Jun; Li, Yong-Jie (Frontiers in Aging Neuroscience, 2016)
Objective: To assess the age-related morphometric changes of subcortical structures in healthy people. Material and Methods: Ultra-high field 7 tesla magnetic resonance imaging in humans was used to visualize the subcortical structures of healthy young, middle-aged, and elderly participants. Using the magnetization-prepared two rapid acquisition gradient echoes sequence, we assessed the visibility of the margins of the thalamus and white matter in the thalamus, as well as the anterior commissure (AC) and posterior commissure (PC) length, the maximal height of the thalamus, the half width of third ventricle, and the distance between the AC and the center of the mammillothalamic tract at the level of the AC-PC plane. All quantitative data were statistically evaluated. Results: The AC-PC length did not differ significantly among the three groups. The maximal height of the thalamus decreased with age (rs(53)=-0.719, p<0.001). The half width of the third ventricle (rs(53)=0.705, p<0.001) and the distance between the AC and the center of the mammillothalamic tract (MTT) (rs(53)=0.485, p<0.001) increased with age. The distance between the AC and the center of the MTT of the young and the elderly participants differed significantly (p=0.007). Conclusion: The AC-PC length is not a good candidate for proportional correction during atlas-to-patient registration. The maximal height of the thalamus and the half width of the third ventricle correlated strongly with age, and the MTT position in relation to the AC shifted posteriorly as age increased. These age-related morphometric changes of subcortical structures should be considered in targeting for functional neurosurgery.